Implementasi program literasi berbasis Tri N di SD Negeri Panggang Tanjungsari - Suliyanti Suliyanti; Siti Rochmiyati (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2023)
This article aims to find out the implementation of the School Literacy Movement (GLS) program based on one of Tamansiswa's teachings, namely Tri N (Niteni, Nirokke, and Nambahi) at Panggang Tanjungsari State Elementary School. This study uses a qualitative approach. Informants or resource persons for this research consisted of school principals, teachers, student guardians, and students of Panggang Kapanewon Tanjungsari Elementary School, Gunungkidul Regency. Methods of data collection in this study using interviews, observation, and documentation. The results of the research conducted show that the School Literacy Movement has been carried out regularly at this school since 2018. At Panggang Tanjungsari State Elementary School, researchers implemented the Tri-N-based school literacy movement from the teachings of Ki Hajar Dewantara, namely Niteni, Nirokke, and Nambahi. The parties involved in supporting the policy of the School Literacy Movement at Panggang Negeri Elementary School are all members of the school community including principals, teachers, staff, students, and parents. The implementation of the Literacy Movement at SD Negeri Panggang based on the teachings of Tri N Ki Hajar Dewantara is carried out through the Reading Corner Program, mandatory library visits, reading time programs, making wall magazines, and writing competitions.